NSP-interacting kinase, NIK: a transducer of plant defence signalling - Santos, Anésia A.; Lopes, Kênia V. G.; Apfata, Jorge A. C.; Fontes, Elizabeth P. B. (Journal of Experimental Botany, 2010)
The NSP-interacting kinase, NIK, belongs to the five leucine-rich repeats-containing receptor-like serine/threonine kinase subfamily that includes members involved in plant development and defence. NIK was first identified by its capacity to interact with the geminivirus nuclear shuttle protein (NSP) and has been strongly associated with plant defence against geminivirus. Recent studies corroborate its function in transducing a defence signal against virus infection and describe components of the NIK-mediated antiviral signalling pathway. This mini-review describes the role of NIK as a transducer of a novel layer of plant innate defence, presents new data on NIK function, and discusses its possible involvement in plant development.
Keywords: Defence signalling; NIK1; NSP-interacting kinases; Nuclear shuttle protein; Receptor-like kinases; Geminivirus